Syenitic and associated intrusions of the Kap Edvard Holm region of Kangerdlugssuaq, East Greenland - Deer, W. A.; Kempe, D. R. C.; Jones, G. C. (Meddelelser om Grønland. Geoscience, 1984)
Kap Edvard Holm, near Kangerdlugssuaq, forms part of one of the six Tertiary igneous centres of southern East Greenland. The plutonic rocks are mainly cumulate gabbros but there are several syenite masses, together with some minor granophyres and other acid rocks. The larger syenites - Kap Boswell, Kap Deichmann, and Hutchinson Gletscher I - are intruded as conical masses into the gabbros with an intermediate ring of igneous breccia. The petrography, mineralogy, and bulk chemistry of the rocks are reported. The syenites are generally nordmarkitic, containing hedenbergite and aegirine-augite, and amphiboles ranging from hastingsite, ferroedenite, and ferrorichterite (katophorite) to arfvedsonite, while aenigmatite is quite common in the Kap Boswell and Barberkniven syenites and veins. Many rock and mineral analyses are given. An estimate of the composition of the parent magma gives a nordmarkitic liquid very close to that of the main peripheral intrusions at Kangerdlugssuaq and also to the quartz trachytic late differentiate of the Azores alkali basalt. This agrees with the authors’ earlier suggestion that all the syenite masses were most probably the products of a quartz trachyte magma, fractionated in the case of the main intrusion to yield the range of rock types occurring there, and itself produced by differentiation of an alkali basalt magma such as yielded some of the many dykes present in the region. An alternative explanation, proposed by Brooks & Gill (1982), that the main intrusion derived from the reaction of a foyaitic magma, fractionated from a nephelinitic parent, with the enclosing gneisses and basalts, could not have been repeated so exactly throughout the minor peripheral intrusions at Kangerdlugssuaq and again at Kap Edvard Holm.